Desdemona’s changing voices: from the “Willow Song” to the “Canzona del Salice” - Chantal Schütz (Sillages Critiques)
The Willow Song in Shakespeare’s Othello involves a complex intertwining of mimetic processes: a boy actor enacts the female Desdemona, who imitates a maid called Barbary singing an old ditty, while the original singer referred to herself as a singing (or sighing) lover sitting at the foot of a tree. The boy’s performance of Desdemona’s death left a lasting impression on early modern audiences, just as Barbary’s singing death did on the character of Desdemona – a detail which enables the dying Emilia to put a finishing touch on the mimetic process by comparing herself to Desdemona, and both of them to the swan, who only sings when she is about to die.The mimetic process was carried further in the 19th century, thanks to the operatic version written by Rossini in 1816. This paper examines the evolution from a metonymical relationship between the theatrical character and its representation by the singer Maria Malibran to a metaphorical relationship that actually substituted Malibran to Desdemona. With the result that the scene, which had purely and simply been excised from the English stage-world, was gradually reintroduced under the influence of the operatic version, thus restoring an adult voice to a character that had long been reduced to a child-bride almost devoid of vocal identity. Verdi’s Desdemona then appears as a fully matured character whose emotional power is fuelled by her vocal prowess.